Acceptability of the Decision Support for Safer Surgery Tool - Norton, Wynne E. (Am J Surg, 2014)
BACKGROUND: We examined providers' perceptions of the Decision Support for Safer Surgery (DS3) tool which provided preoperative patient-level risk estimates of postoperative adverse events. METHODS: The DS3 tool was evaluated at two academic medical centers. During the validation study, surgeons provided usefulness ratings of the DS3 tool for each patient prior to surgery. At the end of the study, providers' perceptions of the DS3 tool were assessed via questionnaire. Data were analyzed using descriptive statistics and independent samples t-tests. RESULTS: During the trial, twenty-three surgeons completed usefulness ratings of the DS3 tool for 1,006 patients. Surgeons rated the tool as Very Useful or Moderately Useful in 251 (25%) of the cases, Neutral in 469 (46.6%) of the cases, and Moderately Un-Useful or Not Useful in 286 (28.4%) cases. At the end of the trial, thirty-two providers completed the questionnaire; perceptions were relatively neutral, although several aspects were rated quite favorably. CONCLUSIONS: The DS3 tool may be most useful for achieving particular tasks (e.g., training novice surgeons; increasing patient engagement) or encouraging specific processes (e.g., team-based care) in surgical care settings.